(untitled) (Sciences & Technology. A, exactes sciences, 2000)
This study presents a new theoretical determination of yield stress for pure mono-crystal materials based on the concept of the Efficient Area of Stress (EAS). From the atomic yield stress on the atomic surface a², given by the model of Orowan, the macroscopic yield stress is then obtained through a Scale Law of Measure (SLM) which depends only on the lattice spacing and a constant L. This relation shows that the efficient atomic dimension is a fractal dimension. The precision obtained by the SLM is of an atomic order compared to the error (102 to 104 MPa) obtained by classical theories. The SLM gives also new theoretical relations for the elastic limit of strain, the toughness and the fracture strength. The SLM is finally extended to non pure materials to take into account the microstructures (grain size, impurity, phases, solutions, etc.) and the temperature effects by introducing the concept of an "efficient atomic distance".